Unemployment and suicide. Evidence for a causal association?. Issue 8 (25th July 2003) - Blakely, T A; Collings, S C D; Atkinson, J
Abstract : Objectives: To determine the independent associations of labour force status and socioeconomic position with death by suicide. Design: Cohort study assembled by anonymous and probabilistic record linkage of census and mortality records. Participants: 2.04 million respondents to the New Zealand 1991 census aged 18–64 years. Main outcome measure: Suicide in the three years after census night. Results: The age adjusted odds ratios (95% confidence intervals) of death by suicide among 25 to 64 year olds who were unemployed compared with employed were 2.46 (1.10 to 5.49) for women and 2.63 (1.87 to 3.70) for men. Similarly increased odds ratios were observed for the non-active labour force compared with the employed. Strong age only adjusted associations of suicide death with the socioeconomic factors of education (men only), car access, and household income were observed. Compared with those who were married on census night, the non-married had odds ratios of suicide of 1.81 (1.22 to 2.69) for women and 2.08 (1.66 to 2.61) for men. In a multivariable model the association of socioeconomic factors with suicide reduced to the null. However, marital status and labour force status remained strong predictors of suicide death. Unemployment was also strongly associated with suicide death among 18–24 year old men. Sensitivity analyses suggested that confounding by mental illness might explain about half, but not all, of the association between unemployment and suicide. Conclusions: Being unemployed was associated with a twofold to threefold increased relative risk of death by suicide, compared with being employed. About half of this association might be attributable to confounding by mental illness.